OPTION VALUATION BY USING FAST FOURIER TRANSFORM (FFT) TECHNIQUES WITH VARIANSI GAMMA(VG) - Rajab, Fitriani (Jurusan Matematika FST-UIN Alauddi Makassar, 2014)
Fourier transform Techniques have important role in Financial Mathematics. Fast Fourier Transformation (FFT) is a technique Fourier transform with high accuracy and more efficient by using characteristic function than density function itself. FFT is used to option valuation under LÃ©vy processes. This journal described Fourier transfor with its properties and LÃ©vy processes. The section LÃ©vy processes, we present a list of LÃ©vy processes commonly used in financial applications together with their characteristic functions. FFT Algorithms is computed by using characteristic function of Variance Gamma (VG) with parameter ð, ð£, ð). At the end, we simulated computing Eropa call option value with FFT technique using VG by Carr and Madanâs approach.